The discussion about slaves in Christian assemblies at the end of Second Century (Circe de clásicos y modernos, 2018)
The aim of this work is to present the Christian perception of slavery in the second half of the second Century from the discussion established between the Christian apologists and the pagan writers about the role of slaves in the spread of Christian religion. The background of the discussion reveals the strong transformations that the Christian communities were undergoing in their search for an identity in the empire. The pagans identified Christianity as a religion promoted by slaves. The leaders of the churches, on the other hand, tried to promote the opposite image: conversion and proselytism was carried out by the masters, not by the slaves.
Keywords: christianity; slavery; conversion; second Century; apologists